Edukasi Microsoft Word dalam Membuat Karya Ilmiah di SMP Negeri 10 Cimahi - Ayu Hendrati Rahayu; Firdhani Faujiyah; Castaka Agus Sugianto; Gerinata Ginting; Dini Rohmayani; Ari Sudrajat; Taufik Fajar Mustafa (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to improve the skills of students at SMP Negeri 10 Cimahi in using Microsoft Word for academic writing purposes. According to reports from the school, many students face difficulties in understanding the functions and usage of word processing software, particularly in composing scientific papers. The activity was conducted over three days through hands-on practical sessions in the school’s computer laboratory, utilizing pre-prepared academic writing templates. The results showed significant improvement in students' technical abilities, although several challenges were encountered, such as lack of basic knowledge about computer hardware and the use of outdated versions of Microsoft Word. The program not only enhanced students' practical skills but also fostered their interest in technology and boosted their confidence in completing academic assignments. It is hoped that similar programs can be implemented more widely to support technology-based learning at the basic education level.